Personalidad y comportamiento no verbal: perfilación indirecta en casos de feminicidio = Personality and nonverbal behavior : indirect profiling in femicide cases - Muñoz-Espinosa, Verónica (Behavior & Law Journal, 2020)
The aim of any criminal investigation is to obtain enough evidence to establish the facts. The interviews carried out by police investigators, victims, witnesses and suspects, are one of the main sources of information available to them. Such is its importance that specific procedures have been developed for taking statements from victims, such as the pre-constituted evidence or the cognitive interview, and the same happens with suspects, for whom interrogation procedures have been developed such as the REID and the PEACE. The interview and the interrogation should be understood as interactions between people (interviewer-interviewee), so the police interviewer must create the most effective strategy based on the person one is dealing with. In this regard, indirect profiling and the relation between personality and nonverbal behavior are important, since they will help to the interviewer to know what type of person (personality) one is dealing with, without using self-reported questionnaires, and avoiding some of the problems linked to direct personality assessment. That is the reason why the aim of this current study is to carry out a pilot study in which the relation between personality and nonverbal behavior is analyzed, by using Eysenck’s PEN model, through a prison sample, consisting of 20 cases of feminicide. Being able to profile indirectly is only part of the process, since once the subject has been profiled; an interview/interrogation strategy should be designed based on the personality subject.